![(x + y)^{3} = x ^{3} + y ^{3} + 3xy(x + y) (x + y)^{3} = x ^{3} + y ^{3} + 3xy(x + y)](https://tex.z-dn.net/?f=+%28x+%2B+y%29%5E%7B3%7D+++%3D+x+%5E%7B3%7D++%2B+y+%5E%7B3%7D++%2B+3xy%28x+%2B+y%29)
Attachments:
![](https://hi-static.z-dn.net/files/d72/5d27afd28df682684852c79e7356386c.jpg)
Answers
Answered by
1
(x + 2)³
=>. x³ +. 2³ + 6x(x+2)
=>x³+ 8 + 6x² + 12x .
.............
Answered by
2
Hope it will help you
Thanks for asking .
..........
ALWAYS HAPPY TO HELP ......
GOOD DAY AHEAD............
Attachments:
![](https://hi-static.z-dn.net/files/dd5/eb1dc14aa15b355f14002c6724c9e811.jpg)
Similar questions